Rhizon sampler alteration of deep ocean sediment interstitial water samples, as indicated by chloride concentration and oxygen and hydrogen isotopes - Madeline D. Miller; Jess F. Adkins; David A. Hodell (Geochemistry, Geophysics, Geosystems)
Abstract Despite their potential to inform past ocean salinity, δ18O, and temperature, high‐resolution depth profiles of interstitial water chloride concentration and hydrogen and oxygen isotopes exist in very few locations. One of the primary limitations to the recovery of these depth profiles is that traditional interstitial water sampling requires 5–10 cm whole rounds of the sediment core, which has the potential to interfere with stratigraphic continuity. The Rhizon sampler, a nondestructive tool developed for terrestrial sediment interstitial water extraction, has been proposed for efficient and nondestructive sampling of ocean sediment pore waters. However, there exists little documentation on the reliability and performance of Rhizon samplers in deep ocean sediments, particularly in regard to their effect on chloride concentration and oxygen and hydrogen isotopic measurements. We perform an intercomparison of chloride concentration and oxygen and hydrogen isotopic composition in samples taken using traditional squeezing versus those taken with Rhizon samplers. We find that samples taken with Rhizons have positive biases in both chloride concentration and stable isotopic ratios relative to those taken by squeezing water from sediments in a hydraulic press. The measured offsets between Rhizon and squeeze samples are consistent with a combination of absorption by and diffusive fractionation through the hydrophilic membrane of the Rhizon sampler. These results suggest caution is needed when using Rhizons for sampling interstitial waters in any research of processes that leave a small signal‐to‐noise ratio in dissolved concentrations or isotope ratios.